1993
DOI: 10.1109/20.281249
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation fields of reversal in oriented and non-oriented barium ferrite media

Abstract: Measurements of time dependent magnetization have been made on samples of partially oriented and non-oriented barium ferrite recording media. From these data and complementary measurements of the irreversible susceptibility, the variation of the fluctuation fleld Xf with applied fleld hae been obtained. For the non-oriented sample the variation is quite broad whereas for the aligned case a rapid variation is found. These different types of behaviour are attributed to the marked differences in the interaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…5,15,16 Patel et al has shown that the δm plots for the powder samples are negative for all fields. 17 On the other hand, we have recently shown that the δm may take both positive and negative values even for powder samples if the grains are in single domain limit and the secondary phases are existent in addition to the main BaFe 12 O 19 phase. 18 Studied samples are neither in single domain limit nor including impurity phases.…”
Section: Resultsmentioning
confidence: 98%
“…5,15,16 Patel et al has shown that the δm plots for the powder samples are negative for all fields. 17 On the other hand, we have recently shown that the δm may take both positive and negative values even for powder samples if the grains are in single domain limit and the secondary phases are existent in addition to the main BaFe 12 O 19 phase. 18 Studied samples are neither in single domain limit nor including impurity phases.…”
Section: Resultsmentioning
confidence: 98%
“…This behavior suggests that the interaction driven changes in the remanence states in the original powder sample occurs faster than the less concentrated ones. Again this can be attributed to a positively dipolar coupled particles (stacked) [3,4]. Accordingly, the DM profile is observed to become more negative as the original powder becomes less concentrated.…”
mentioning
confidence: 84%
“…This technique is based on the wellknown Wohlfarth relation and gives the interaction driven changes in the remanence states M d and M r : Positive DM profile is known to arise from magnetizing (stabilizing) interactions whereas negative DM profile arises from demagnetizing interactions. For barium ferrite media, positive and negative DM profiles were observed for oriented and non-oriented systems of particles, respectively [3]. The effects of particles shapes and orientations on the magneto-static interactions have been modeled and shown that the DM profile (positive or negative) critically depends on the shape and particle arrangements in the system [4].…”
mentioning
confidence: 97%
“…Dicho comportamiento puede asociarse al elevado desorden estructural presente en las muestras y la existencia de regiones donde se presentan interacciones que conducen a una inversión cooperativa de la magnetización [5,6]. En la muestra M5 con un contenido más alto de MQP-Q, los valores más elevados de Δm(H) en la región con interacciones magnetizantes reflejan el acoplamiento por intercambio entre los nanogranos de NdFeB y αFe.…”
Section: Bibliografíaunclassified